If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -48 = 12x + -4 Reorder the terms: -48 + 12x = 12x + -4 Reorder the terms: -48 + 12x = -4 + 12x Add '-12x' to each side of the equation. -48 + 12x + -12x = -4 + 12x + -12x Combine like terms: 12x + -12x = 0 -48 + 0 = -4 + 12x + -12x -48 = -4 + 12x + -12x Combine like terms: 12x + -12x = 0 -48 = -4 + 0 -48 = -4 Solving -48 = -4 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -4(6y-7)-y=-3(y-2) | | 1/3x-4=y | | 3[6-(-9x-7)]=216x+186 | | x^3+7x^2-5x^2-5x-35= | | 16-8x=14-7x | | 4(n+5)=-n+2(n-2) | | 4-4x-3=x^2 | | 5(x-1)-2(2x+3)=5x-4 | | 9(3x-1)-5=20x | | 172=125-x | | 5t^2+2=7t | | (2/3x+x)+16=102 | | m-9=1.1 | | 4x+29=2x+15 | | y-62500=0.25x | | -3+3(1+4)=6(-6+3n) | | 165=-y+43 | | 7x-(3x+6)=5x-35 | | 5x^3-5= | | x^2-4.9x+2.1=0 | | y=1/7x+75.5 | | x-62500=0.25(125000) | | 18x-15=-21+12 | | 6x-11=-21+12x | | 4x-16=7x+5 | | -(x-3)=-5+3(3x-4) | | 2x(x-2)-1=4-4x(x+3) | | 5x-250= | | x^5-2x^4+7x^3+22x^2-92x+40=0 | | 9h-(h^2-4h+1)=48-h^2 | | 5x-4=9x+8 | | 100+15x=75+17x |